Remake, remodel : women's magazines in the digital age - Duffy, Brooke Erin (Urbana : University of Illinois Press, 2013)
What is a magazine? For decades, women's magazines were regularly published, print-bound guidebooks aimed at neatly defined segments of the female audience. Crisp pages, a well-composed visual aesthetic, an intimate tone, and a distinctive editorial voice were among the hallmarks of women's glossies up through the turn of this century. Yet amidst an era of convergent media technologies, participatory culture, and new demands from advertisers, questions about the identity of women's magazines have been cast up for reflection. This title offers a unique glimpse inside the industry and reveals how executives and content creators are remaking their roles, their audiences, and their products at this critical historic juncture.
Making the magazine : three hundred years in print -- Transforming the magazine : from print to bits -- Production tensions : new positions, routines, and gender roles -- Rethinking readership : the digital challenge of audience construction -- Inviting audiences in : interactive consumers and fashion bloggers -- Off the page : medium-specific approaches to content.
Includes bibliographical references (pages 159-179) and index.
Description based on print version record.
English.
eBooks on EBSCOhost
Keywords: Women's periodicals -- History -- 21st century; Women's periodicals -- Publishing; Women's periodicals -- Marketing; Women's periodicals -- Effect of technological innovations on; Presse féminine -- Histoire -- 21e siècle.; Presse féminine -- Édition.; Presse féminine -- Effets des innovations sur; REFERENCE -- Yearbooks & Annuals; SOCIAL SCIENCE -- Media Studies; Periodicals -- Publishing; Women's periodicals; Women's periodicals -- Publishing; 2000-2099; Electronic books; History